(untitled) (JURNAL KEPERAWATAN, 2018)
Abstrack : Introduction: Family support is a support that is beneficial to the individual gained from his family and self-esteem is the result of an assessment of individual acceptance or rejection of himself. Purpose: This study aims to identify the relationship of family support to the self-esteem of breast cancer patients undergoing chemotherapy in the Pomegranate Room RSUP.Prof.Dr.R.D. Kandou Manado. Sample: This study was conducted to 52 breast cancer patients who underwent chemotherapy. Research Design: This research is cross-sectional research which is descriptive correlative, with slovin technique. Results Conclution: The research instrument is a questionnaire that includes demographic data and statements regarding family support and self-esteem. Data collection took place during March until April 2018. The correlation test used in this research is Chi Square correlation test. The results of the study showed that family support had significant relation with self-esteem of breast cancer patients who underwent chemotherapy in the Pomegranate Room of RSUP. Prof.Dr.R.D. Kandou Manado, the strength of good relationship and positive pattern (p = 0,000). Conclusion: It can be concluded that the higher the family support the higher the self-esteem of breast cancer patients undergoing chemotherapy in the Pomegranate Room of RSUP. Prof.Dr.R.D. Kandou Manado. Key Words : Family Support, Self-Esteem, Breast Cancer , Chemotherapy Abstrak : Pendahuluan: Dukungan keluarga adalah suatu dukungan yang bermanfaat bagi individu yang diperoleh dari keluarganya dan harga diri merupakan hasil penilaian berupa penerimaan atau penolakan individu terhadap dirinya sendiri. Tujuan: Penelitian ini bertujuan untuk mengidentifikasi hubungan dukungan keluarga dengan harga diri pasien kanker payudara yang menjalani kemoterapi di Ruang Delima RSUP.Prof.Dr.R.D. Kandou Manado. Jumlah sampel: Penelitian ini dilakukan kepada 52 pasien kanker payudara yang menjalani kemoterapi . Desain Penelitian: Penelitian ini adalah penelitian cross-sectional yang bersifat deskriptif korelatif. Hasil Penelitian: Uji korelasi yang digunakan dalam penelitian ini adalah uji korelasi Chi Square. Hasil penelitian menunjukan nilai (p=0,000) yang berarti Ha diterima atau ada hubungan dukungan keluarga yang signifikan dengan harga diri pasien kanker payudara yang menjalani kemoterapi di Ruang Delima RSUP. Prof.Dr.R.D. Kandou Manado, kekuatan hubungan baik dan berpola positif (p= 0,000 ). Simpulan: Dapat disimpulkan bahwa semakin tinggi dukungan keluarga maka semakin tinggi harga diri pasien kanker payudara yang menjalani kemoterapi di Ruang Delima RSUP. Prof.Dr.R.D. Kandou Manado. Kata kunci : Dukungan keluarga, harga diri, kanker Payudara, Kemoterapi